Penguatan Kelembagaan Sosial, Manajemen Organisasi dan E-Marketing untuk Mendorong Perkembangan Kelompok Desa Wisata di Kelurahan Tegaltirto - Endang Susilowati; M. Agung Nugroho (Jurnal Maksipreneur, 2014)
In addition to being an additional new tourist destinations, Desa Wisata in DIY turns out to function as well as one of conservation and community empowerment strategies for environment and culture. Through the development of community Desa Wisata has a new source of income while preserving they environment and culture. In that context, the development of Desa Wisata has a very strategic position. In terms of potential, DIY has many villages are ready to develop into Desa Wisatabecause they have material that can be packed into tourist attractions and also supported by the strong desire of the community to develop itself into a Desa Wisata. But however potential alone is not enough, because it must be driven by a reliable institutional managers to promote Desa Wisata on market. This problem is also faced by the Desa Wisata Tegaltirto Kec. Berbah Kabupaten Sleman. This community service activities aimed to encouraging institutional strengthening Desa Wisata and e-marketing capabilities of the managers and developer. Training and mentoring activities carried out in Dusun Karangwetan with 20 participants (5 groups). Training held for two full days, and will be assisting the manager and developer of this institution. Marketing tools in the form of two units complete with modem netbook is expected to accelerate e-marketing capabilities of this group.